Sectoral Structure and Entry Regulations - Julián Messina (Institute for the Study of Labor (IZA), 2003)
The sectoral allocation of labor differs considerably across developed economies, even in the presence of similar patterns of structural change. A general equilibrium model that captures the stylized facts of structural change is presented. In this framework, economy-wide barriers to entry hinder the development of dynamic sectors such as service industries. Moreover, higher service prices and rents in regulated economies reduce labor supply, providing a rationale for the negative association between product market regulations and the employment rate previously found in the literature. Empirical evidence presented shows that regulatory entry barriers help explaining differences in the sectoral allocation of labor across OECD countries.
Keywords: L5; O41; O11; 330; unbalanced growth; entry regulations; sectoral employment; Sektorale Beschäftigungsstruktur; Allgemeines Gleichgewicht; Mehr-Sektoren-Modell; Einkommenselastizität; Markteintritt; Dienstleistungssektor; Regulierung; Schätzung; Theorie; OECD-Staaten